Experiment on Shock Wave Control of a Hypersonic Vehicle Standard Model Based on Plasma Synthetic Jet - Wei XIE; Guotun HU; Wei SHI; Yan ZHOU; Hongbo LU; Zhenbing LUO (气体物理)
The novel active flow control technology based on plasma synthetic jet (PSJ) has great application potential in the field of shock wave control due to its advantages such as no gas source, strong control ability, and wide excitation frequency band. The control effect of single-pulsed PSJ on head bow shock and wing shock of a hypersonic vehicle model and the drag reduction effect were experimentally studied in a hypersonic wind tunnel. The results show that the opposing PSJ can significantly increase the standoff distance of the head bow shock, and the transverse PSJ can basically eliminate the wing shock completely. The maximum instantaneous drag reduction rate of the vehicle measured by the dynamic force sensor is about 15.5%, but the drag change measured by the sensor has a delay of about 250 μs. The influence of discharge energy, incoming flow total pressure, exit diameter, and cavity volume on the control effect of the head bow shock was also studied.